The stewardship of ‘Taiwan’s Economic Miracle’ and its feedback on national cultural context - Tzu-hsuan Kuo (State University of Management, 2021)
Poverty – prosperity leap debates have been rising steeply across the globe in recent decades. Taking Taiwan with its Li Kwohting’s legacies as a good illustration how the agrarian-based colony turned into the ‘Silicon Island’ for a comparatively small period the authors analyse the man-made policies on making the ‘Taiwan’s Economic Miracle’. The article studies a ‘twilight zone’ within the gap as well as both the prerequisites and outcomes of the ‘Taiwan’s Godfather of Technology’ stewardship. The paper also considers the factors which determine the rapid growth of Taiwan.Despite the almost universal characteristics of the East Asia countries, differences between them remain substantial. This circumstance gives the authors a room for speculations over the reasons of one country becoming the world leaders. The authors use the ‘Four Asian Tigers’ as Hong Kong, Singapore, South Korea and Taiwan for comparison. China is also included in the comparative analysis for better understanding. The study showed that the success phenomenon of the country is being determined in the national cultural context, inside of which the economy develops. The Geert Hofstede’s Six Cultural Dimensions model was utilized for employing the indexes as follows: Power Distance, Collectivism vs. Individualism, Uncertainty Avoidance Index, Femininity vs.Masculinity, Short-Term vs. Long-Term Orientation and Restraint vs. Indulgence. The cultural dimensions typology of the Geert Hofstede helped to explain the national predominance for this or that economic and political initiatives of the government, the comparison showed that the core of nation’s prosperity development mechanisms is incorporated in the Taiwanese cultural code.